Biogenesis, function, and landscape of tsRNAs in central nervous system diseases - Kaiying Yang; Yu Sun; Jie Zhao; Chang He; Xudong Pan; Xiaoyan Zhu (Wiley, 2023)
Abstract Transfer RNA‐derived small RNAs (tsRNAs) are fragments that originate from mature or precursor tRNAs and are a subclass of sRNAs. With the development of high‐throughput sequencing techniques, the real feature of tsRNAs has gradually been revealed. tsRNAs are functional fragments of distinct lengths produced by the cleavage of mature or precursor tRNAs by different ribonuclease enzymes. tsRNAs exert extensive functions, including gene silencing, translational regulation, and reverse transcriptional regulation, affecting cell viability and differentiation and participating in pathological processes of various diseases, including central nervous system (CNS) diseases. Emerging sequencing evidence indicates that tsRNAs are expressed differently in various CNS diseases, preliminary suggesting that tsRNAs are involved in the occurrence and progression of neurodegenerative diseases, stroke, glioma, epilepsy, and other CNS diseases. In addition, significant differences expression of extracellular tsRNAs in circulating or cerebrospinal fluid between patients and normal individuals have demonstrated the diagnostic and prognostic value of tsRNAs as biomarkers for liquid biopsy. In this review, we provide a detailed summary of the biogenesis, function, and chemical modification of tsRNAs, focusing on the current status and prospects of research on tsRNAs in neurodegenerative diseases, stroke, glioma, epilepsy, and others.